The influence of the quality in daycare environments on children's motor development between six to 15 months old - Keli Lovison; Helenara Salvati Bertolossi Moreira; Joselici da Silva; Luiz Guilherme Dacar Silva Scorzafave; Débora Falleiros de Mello (Instituto Materno Infantil de Pernambuco, 2021)
Abstract Objectives: to analyze the influence of the quality in the environment on children's motor development between six to 15 months old attending early childhood education centers. Methods: a cross-sectional and analytical study addressing children's motor development between six to 15 months old, both sexes, enrolled in nursery (0-12 months) and preschoolers (12-24 months). The Affordances in the Home Environment for Motor Development-Infant Scale and Alberta Infant Motor Scale were used in the Brazilian versions Results: the sample was comprised of 104 children and 30 early childhood education centers: presenting a mean age of 9.15 months, 88% attended full-time and 12% part-time schooling (mornings or afternoons). One center was classified with a low Affordances, 26 were considered Sufficient, and three were Adequate. Of the participating children, 40% presented typical motor development. The higher levels of Affordances suggest better motor development, and lower levels of suspected delayed motor development. Conclusion: the environments of early childhood education centers influence children's motor performance, especially daily activities and the use of toys. The lower the Affordances level, more likely children are suspected of delayed motor development.